The role of glutamine in supporting gut health and neuropsychiatric factors - Brett J. Deters; Mir Saleem (Food Science and Human Wellness)
Recent research has shown that the amino acid glutamine can positively affect gut health by supporting the gut microbiome, gut mucosal wall integrity, and by modulating inflammatory responses. As modulated by the vagus nerve, via the enteric nervous system, the gut-brain connection can impact the brain's neurochemical environment. Poor gut health can disrupt the balance of neurotransmitters, which can result in neuropsychiatric based conditions such as depression. Glutamine supplementation may provide significant adjunctive nutritional support in cases of depression by promoting proper gut health and function.